1966
DOI: 10.1099/00221287-42-1-115
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Wall Deficiencies in L-forms of Staphylococcus aureus

Abstract: SUMMARYThree strains of penicillin-induced and one strain of D-cycloserineinduced L-forms of Staphylococcus aureus were investigated for components of the normal bacterial cell wall. None of the 4 strains was found to contain more than 0.008 yo of its dry weight as muramic acid, indicating the lack of mucopeptide. These forms also lacked the cell-wall ribitol teichoic acid as shown by the failure to yield any material containing ribitol. Neither muramic acid nor ribitol was detected as acid-soluble nucleotides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1967
1967
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Immunization with Staphylococcus aureus induced antibodies which gave weak fluorescence with both coagulase-negative variants and L-forms. Identical antigens have been found in extracts of the membranes of the coccal form and the L-form of S. aureus (Pratt, 1966). Absorption of antisera with either encapsulated or nonencapsulated, coagulase-positive staphylococci eliminated the fluorescent reaction of L-forms.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Immunization with Staphylococcus aureus induced antibodies which gave weak fluorescence with both coagulase-negative variants and L-forms. Identical antigens have been found in extracts of the membranes of the coccal form and the L-form of S. aureus (Pratt, 1966). Absorption of antisera with either encapsulated or nonencapsulated, coagulase-positive staphylococci eliminated the fluorescent reaction of L-forms.…”
Section: Discussionmentioning
confidence: 96%
“…Gorrill, Klyhn & McNeil(1966) found that clumping factor was either destroyed or removed by sonic vibrations. A remnant of cell-wall material may be present on some or all of the so-called L-forms of S. aureus (Pratt, 1966;Hamburger & Carleton, 1966); clumping factor could be a component of this cell-wall remnant. Coagulase and clumping factor are closely associated in the bacterial form of typical S. aweus strains, and L-forms of these strains are known to produce coagulase (Mattman, Turnstall & Rossmoore, 1961).…”
Section: Introductionmentioning
confidence: 99%
“…As far as staphylococcal protein A has been found to be involved in the bacterial–host cell interactions (Jung et al , 2001), its reduction may contribute to atypical properties of these forms in vivo and modification of infection induced by them. Differences in the production of protein A by normal S. aureus and L‐forms, as a significant reduction of muramic acid, indicating the lack of mucopeptide, and also lack of cell‐wall ribitol teichoic acid in L‐forms of S. aureus were also reported (Pratt, 1966; Forsgren, 1969). It is known that cell wall (or cytoplasmic membrane of L‐forms) as a surface organelle function allows bacterial pathogens to interact with their environment, in particular the tissues of the infected host.…”
Section: Discussionmentioning
confidence: 99%
“…Rabitol, polysaccharide A and muramic acid were also completely absent in both cycloserineinduced and penicillin-induced CWDB from Staphylococcus aureus. 38 In addition, low galactose concentrations caused a strain of Bifidobacterium to lose the ability to synthesize a rigid murein, 39 and a stress protein in CWDB cultures from Escherichia coli was not present in cultures of WTB. 40 A residual cell wall persists in most CWDB and revertants.…”
Section: Life Cyclementioning
confidence: 99%